Prevalence of the double burden of malnutrition and its association with ideal cardiovascular health in Brazilian children - Raytta Silva Viana; Marcus Vinicius Nascimento-Ferreira; Augusto César Ferreira De Moraes (PLoS ONE, 2026)
Introduction The Double Burden of Malnutrition (DBM), characterized by the coexistence of overweight/obesity and nutritional deficiencies, represents a growing risk to child health, affecting Ideal Cardiovascular Health (CVH). This study aimed to assess the prevalence of DBM and examine its association with CVH. Methods The SAYCARE study was conducted in public and private schools in São Paulo and Fortaleza, including children aged 3–10 years. CVH was evaluated based on the eight components recommended by the American Heart Association. DBM was defined as the coexistence of overweight/obesity (classified by BMI according to age- and sex-specific percentiles) and iron deficiency (serum ferritin concentration <50 µg/L). Data collection included parent questionnaires, anthropometric assessments, accelerometer measurements, blood pressure, and blood samples. Descriptive statistics and multilevel Poisson regression models were applied to estimate prevalence ratios (PR) with 95% confidence intervals (95% CI), with p < 0.05 considered significant. Cluster analyses were also performed using hierarchical and non-hierarchical methods. Results The sample included 611 children, of whom 35.96% had low CVH. DBM was identified in 4.45% of the children, characterized by the coexistence of overweight/obesity and iron deficiency. Children with overweight had a 43.06% prevalence of low CVH, while those with obesity had 49.06%. Poisson regression analysis found no significant associations between DBM and CVH; however, factors such as maternal education and family income positively influenced CVH. Conclusion This study showed that most Brazilian children present moderate to high cardiovascular health, although a significant proportion remains at risk due to factors such as poor diet, sedentary behavior, and excess weight. The presence of DBM highlights the complexity of the nutritional transition in Brazil. Although no significant association between DBM and CVH was found, multifactorial interventions are needed to address the social, behavioral, and biomedical determinants of cardiovascular health in childhood.